2006
DOI: 10.1007/s10350-006-0681-4
|View full text |Cite
|
Sign up to set email alerts
|

Enterostomy Site Hernias: A Clinical and Computerized Tomographic Evaluation

Abstract: Parastomal hernia and closed ostomy site incisional hernias have a high incidence, and computerized tomography has been shown to be a valuable diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 17 publications
3
141
0
10
Order By: Relevance
“…The PRISMA flow diagram is shown in addendum 3 (Key Question A). Fifteen records were included in the qualitative analysis [3][4][5][6][50][51][52][53][54][55][56][57][58][59][60]. Only four studies were retained as High Quality and are listed in the Summary of Findings table (Table 2) [5, [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram is shown in addendum 3 (Key Question A). Fifteen records were included in the qualitative analysis [3][4][5][6][50][51][52][53][54][55][56][57][58][59][60]. Only four studies were retained as High Quality and are listed in the Summary of Findings table (Table 2) [5, [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…The use of imaging methods, such as ultrasonography (US) or computed tomography (CT), may have contributed to the high PSH rates reported during the last years because they can detect smaller hernias that are not apparent at clinical examination [2,4,6]. Cingi et al [12] reported a PSH incidence of 52% at physical examination, while it was up to 78% with the addition of CT scan. Although majority of parastomal hernias most commonly occur within the irst 2 years, the risk of herniation persists for up to 20 years following stoma creation [3,6].…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…However, in case of doubt, imaging studies such as CT scan and US should be performed as an adjunct to clinical evaluation [2,4,10,12,18,19] (Figure 2). Assessment of the patient in the upright and supine positions is important for an adequate physical examination.…”
Section: Clinical Features Diagnosis and Classiicationmentioning
confidence: 99%
“…Tiene una elevada prevalencia (entre 0 % y 56 % según la bibliografía publicada 3,5,6 ), pero es difícil estimar su prevalencia real por el uso de definiciones 6,7,8,9 y criterios diagnósticos diferentes en función del grupo 7,8,9 . Con la utilización de la tomografía computarizada se detectan mayor número de HP que con la exploración clínica exclusivamente 7,10,11 , y llega hasta el 93.8 % con el estudio combinado 12 . También la realización del tac en reposo, durante una maniobra de Valsalva o en prono, puede modificar el porcentaje de HP.…”
Section: Definición Y Prevalenciaunclassified